Decolorization of methylene blue by new fungus: Trichaptum biforme and decolorization of three synthetic dyes by Trametes hirsuta and Trametes gibbosa - Eshghi, Hossein; Alishahi, Zahra; Zokaei, Mahmood; Daroodi, Aboulfazl; Tabasi, Elahe (European Journal of Chemistry, 2011)
In order to screen dye decolorization by Trametes hirsuta, Trametes gibbosa and new fungus Trichaptum biforme, Methylene Blue (MB), Methyl Green (MG) and Reactive Black 5 (RB5) were studied in Broth culture at concentrations of 25, 50 and 70 ppm. Decolorization of these three kind dyes by T. hirsuta decreased by increasing of concentration. Decolorization of RB5 by T. hirsuta was examined in two different medium contains of Mn2+ or veratryl alcohol (VA), as activators. At the presence of laccase activator (VA), RB5 was decolorized 91% at concentration of 70 ppm, and in the medium contains of MnP activator (Mn2+), dye was decolorized less than 50% at same concentration. Decolorization of RB5 by T. hirsuta was more than decolorization of dye at the presence of MnP activator (Mn2+). T. gibbosa decolorized MB, MG and RB5 more than 80% in the presence of MnP activator. Decolorization of the three kind dyes by T. gibbosa, was independent of concentration. T. gibbosa decolorized different dyes during 20 days and T. hirsuta did it during 32 days, this is due higher potential of decolorization of synthetic dyes for T. gibbosa than T. hirsuta. Decolorization of MB by new fungus T. biforme was studied in two medium contains of MnP activator and laccase activator. Rate of decolorization in the presence of MnP activator was more than decolorization in the presence of laccase activator. Decolorization of MB by new fungus T. biforme was higher than decolorization of MB by two other fungi.